Uji Aktivitas UV Protektif Secara In Vivo pada Krim dari Bahan Aktif Cangkang Telur Ayam Ras Menggunakan Hewan Coba Kelinci Betina - Usman, Yusnita; Muin, Rahmatullah (Sam Ratulangi University, 2022)
Previously, an in vitro study of the SPF value of a cream formulation with active ingredients from broiler eggshells was conducted using UV-vis spectrophotometry at a wavelength of 290-320 nm and obtained an SPF value of 8.335 at a concentration of 9000 ppm. This study aims to continue testing the UV protective activity in vivo on creams from these active ingredients with combination of adding 5% titanium dioxide. The experimental animals used consisted of 12 female rabbits divided into 4 groups, namely (1) positive control: market product spf 15, (2) Negative control: cream base, (3) Formula I: (15% egg shell), and (4 ) Formula II: (a combination of 15% eggshell and 5% titanium dioxide). The activity test was carried out by determining (SPF) against UV-B rays in vivo in 4 groups of experimental animals by comparing the Minimum Erythema Dose (MED) value on protected skin with those not protected by sunscreen. The test results were then analyzed based on the category of sunscreen uv protection. The results showed the SPF value of Group 1; 2; 3 and 4 respectively 15.3; 0 ; 8.55 and 12.37. Group 4 has the same activity as group 1 and has better activity than group 3.